Economics and marijuana consumption, pricing and legalisation - Clements, Kenneth W. 1950-; Zhao, Xueyan 1971- (Cambridge University Press, 2009)
"Do marijuana users cut back on consumption when the price rises? To what degree is marijuana consumption related to drinking and tobacco usage? What would happen if marijuana were legalised and taxed in the same way as alcohol and tobacco? Is marijuana priced in a similar way to other goods? Economics and Marijuana deals with these and other questions by drawing on a rich set of data concerning the consumption and pricing of marijuana in Australia, a country where the drug has been decriminalised in some, but not all, states. The book applies the economic approach to drugs to analyse consumption, pricing and the economics of legalising the use of marijuana. The result is a fascinating analysis of this widely used, but little understood illicit drug that provides much needed information and policy advice for a wide range of readers, including economists, policy makers and health professionals" -- Provided by publisher